Sources and Management of Sustainable Waste - Abduh, Natsir (British Journal of Healthcare and Medical Research, 2019)
The research aims to find out the source of garbage from various object activities and find out the waste management system at Sultan Hasanuddin International Airport, Makassar South Sulawesi Indonesia. The study was conducted in September 2015 at Sultan Hasanuddin International Airport in Makassar, South Sulawesi through a survey in the form of interviews, direct observation. Taking and measuring samples at places where there are human activities and points that are considered to represent samples, such as in public services. The focus of research is on the Land Side of the Airport based on the SNI 19-3964-1994 method. which is used in this research is a quantitative approach by calculating the weight and volume of waste generation from each sample point. Of the ten samples observed, the waste generation was obtained at; check in area 74.8 ltr, departure area 20.06 ltr, arrival area 46.8 ltr, public service 96.6 ltr, service office 2.42 ltr, luaggage 52.4 ltr, cargo 208 ltr, minimarket / café 87.3 ltr, restaurant 155.3 ltr and vehicle parking 231.4 ltr. The waste management system is carried out through the 3R method; namely Reduce: 27.29% waste management, Reuse: 36.37% waste management, Recycle: 33.7% waste management and the remaining 2.64% waste is disposed of to landfills.